STUDI KELAYAKAN WILAYAH PEMBANGUNAN PELABUHAN PERIKANAN MOROTAI, PROVINSI MALUKU UTARA - Mutmainnah, Mutmainnah; M. Sangadji, Ikram; Harahap, Zulham; Karman, Amirul (FAPETKAN UNTAD, 2012)
Planning a fishing port requires knowledge and calculations carefully. Various factors such as technical and non-technical related to determining the location covering oceanographic of the region and the state of natural resources in the region to be awakened for port development activities need to be planned. Survey activities conducted in October – November 2006 is located in Morotai Island of North Halmahera Regency, North Maluku Province. Data acquired include administrative data and administrative ownership of the area, physical environment condition data including climate studies, landscapes, hydro-oceanographic condition of the region as well as socio-economic data of population in the region and surrounding areas. Data were obtained indicating that the area can be proposed for fishing port development activity to the national scale in the Tiley beach, Tiley village of Morotai South-West Regency, North Halmahera. Key words : Fishing port, hydrooceanographic, climate.